The Effectiveness of Cooperative Learning-Jigsaw Model to Enhance Students’ Speaking Ability: an Experimental Study At XI Grade of MAN 1 Mataram - Ilham Rahmatullah; Muhammad Amin; Dewi Satria Elmiana (Jurnal Indonesia Sosial Teknologi, 2024)
Studying English is something that is mandatory in many countries including Indonesia since English is one of the most generally spoken languages in the world today. However, mastering English is not easy especially for Speaking. This study focuses on seeing the effect of the Jigsaw on speaking ability since it reflects the performance of the students in order to provide provisions to face a real-world circumstance. This study aims to offer valuable insights for future researchers and teachers focusing on enhancing speaking skills or conducting research utilizing the Cooperative Learning-Jigsaw Model. This study used the Pre-experimental design, so the sample that was used was only one class. The use of Jigsaw influences students' involvement in speaking and increases their communication skills as indicated by significant differences in the pre-test and post-test scores tested using SPSS 23.  In the result of pre-test, there only one student managed to reach “very good” category and no student was able to reach the "excellent" categories. In contrast to the results of the post-test, there were 11 students who succeeded in achieving the "good" category, 9 students achieved the "very good" category and 1 student succeeded in achieving the "excellent" category which shows a significant improvement. Based on the results of hypothesis testing using the Paired T-Test, the Sig was known, namely 0.000 < α (0.005), which means the Null Hypothesis was rejected and the Alternative Hypothesis (Ha) was accepted. Therefore, the Jigsaw model was effective in enhancing students’ speaking ability.